The Amniotic membrane burrito wrapping technique for surgical repair of closed rupture Tendoachilles - A case report - Elshahhat, Amr Ahmed Mahmoud (Journal of the Foot & Ankle, 2024)
After surgical repair of TA rupture, peritendinous adhesions may arise with a potential to re-rupture. The best way to prevent peritendinous adhesions is not well known, even though they can occur after open, mini-invasive, or percutaneous repair procedures. This case report aims to document the efficacy of the human amniotic membrane burrito wrapping (AMBW) technique in repairing acute closed TA rupture over an extended follow-up period, considering tendon healing, gliding, and re-rupture prevention. Level of evidence IV; Therapeutic studies; Case Report.